ЕТИЧНИЙ ТЕЗАУРУС ЯК СКЛАДОВА ТЕОРЕТИЧНОГО КОМПОНЕНТУ ШКІЛЬНОГО КУРСУ (Педагогіка вищої та середньої школи, 2007)
In article separate components in structure of textbooks on ethics for pupils 5-6 classes of general educational high school are characterizedfrom the point of view of a problem of formation of concepts at lessons of ethics.